Controlled Snacking and Peanut Consumption Reduces Caloric Intake in Adolescents - Vinall, Phil (MD Conference Express, 2014)
The Family Lifestyle and Overweight Prevention Program [FLOW; NCT00454610] reported that Mexican American children who snacked on peanuts at least once a week were less likely to be overweight or obese, had lower body mass indices (BMI), and had lower levels of total blood cholesterol. This article discusses some of the details from the FLOW program, other weight management strategies, as well as the role of snacking in weight control.